Feeding practices and nutritional status of children age 6-23 months in Myanmar: Further analysis of the 2015-16 Demographic and Health Survey - Mya, Kyaw Swa; Kyaw, Aung Tin; Tun, Thandar (DHS Working Papers No. 136, 2018)
Nutritional deficiencies are a major problem among developing countries such as Myanmar. They can occur in all age groups, but the impact is more severe among children age 6-23 months as this period is critical for child development, and irreversible damage can occur due to consequences of nutritional deficiencies. Proper infant and young child feeding (IYCF) practices are pivotal to tackle nutritional problems and to prevent irreversible consequences among children. To assess the current feeding practices among children age 6-23 months and associations with their nutritional status, we conducted a secondary data analysis using the 2015-16 Myanmar Demographic and Health Survey. A total of 1,222 children age 6-23 months were included in this analysis. Twenty percent of children were stunted and 43% were moderately anemic. Regarding IYCF practices, only 16% of children received a minimum acceptable diet, 25% received diverse food groups, 58% were fed with minimum meal frequency, 85% currently breastfed, and 59% consumed iron-rich foods. Breastfeeding reduced the odds of being stunted. By background characteristics, male sex, perceived small birth size, children of short stature, and children of working mother were significant predictors of stunting. Iron-rich food consumption was inversely associated with moderate anemia. Among covariates, male sex and maternal anemia were also significant predictors of moderate anemia among children age 6-23 months. The study concluded that stunting and anemia among young children in Myanmar are major public health challenges that need urgent action. Children should be fed with diverse food groups including iron-rich foods according to the World Health Organization (WHO) complementary feeding guidelines. While further prospective research is needed to determine the effect of feeding practice on linear growth, interventions such as iron supplementation, deworming, and nutritional education programs could help prevent stunting and childhood anemia and might reduce their prevalence in Myanmar.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This study was carried out with support provided by the United States Agency for International Development (USAID) through The DHS Program (#AID-OAA-C-13-00095). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.